IDENTIFIKASI SENYAWA ANTIOKSIDAN EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) : EKSTRAK KULIT BUAH MANGGIS - Saristiana, Yuneka; Wahdi, Achmad; Prasetyawan, Fendy (LPPM STIKes Bahrul Ulum Jombang, 2024)
This study aims to identify the antioxidant classes in mangosteen rind (Garcinia mangostana L.), which is known to be rich in natural antioxidants. Antioxidants are compounds that can prevent or slow down cell damage caused by free radicals, which can form through metabolism or environmental exposure. The identification and utilization of natural sources of antioxidants are crucial for protecting cells from damage and supporting health. The research process began with the drying and grinding of mangosteen rind into a fine powder, which was then extracted using ethanol to obtain an antioxidant-rich extract. Subsequently, several phytochemical tests were conducted to identify antioxidant classes such as flavonoids, phenolic compounds, and tannins in the extract. The antioxidant activity assay was performed using the DPPH method, an in vitro method to measure antioxidant activity based on the color change of the DPPH solution that reacts with antioxidant compounds. The extract of mangosteen rind contains alkaloid, flavonoid, saponin, tannin, and steroid compounds. Additionally, the extract of mangosteen rind has potential as an antioxidant with an IC50 value of 48.9685 µg/mL.